Efektivitas Elemen Gamifikasi dalam Virtual Economy Simulation Model (VESM) terhadap Motivasi Belajar Mahasiswa - Rulita Nurfaizana, Della; Andayani, Endah; Yudiono, Udik; Anam, Choirul (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
The advancement of digital technology in higher education has driven a transformation in learning methods that demand active participation and intrinsic motivation among students. This study aims to analyze the effectiveness of gamification elements in the Virtual Economy Simulation Model (VESM) on the learning motivation of university students majoring in Office Administration Educationin Universitas Negeri Malang. The VESM model was developed with four main gamification components: points, badges, leaderboards, and real-time feedback. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sample involved 70 students (Offerings A and E) enrolled in the Introduction to Economics course. The analysis results showed that all indicators were valid (loading factor > 0.70), with high reliability (α = 0.91; CR = 0.94) and an R² value of 0.742, indicating that 74.2% of the variance in learning motivation was explained by the gamification elements. The path coefficient (β = 0.861, t = 19.432, p < 0.001) demonstrated a significant effect. The feedback element contributed most dominantly (β = 0.699), followed by points (β = 0.642), leaderboard (β = 0.613), and badges (β = 0.571). These findings confirm that the implementation of gamification in VESM effectively enhances university students’ learning motivation and has the potential to become an innovative interactive learning model in economics education.